2017
DOI: 10.5194/hess-2017-424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of lumped hydrological balance models in peninsular Spain

Abstract: Abstract. The assessment of inflows in a water resources system is essential for the appropriate analysis of its management.These inflows can be obtained from hydrological balance models. In this paper, we intend to perform a comparative study of six lumped hydrological balance models in several basins with different climatic conditions within Spain. Lumped models enable the estimation of catchment resources without using spatially distributed information that would not be available in 10 many cases. We have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…After analysing these results, it was concluded that both SWAT and ANN were suitable. The more arid the catchment, the lower the performances obtained in the hydrological models, which is similar to the experience reported by Pérez-Sánchez et al, (2017) [61].…”
Section: Comparison Of Model Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…After analysing these results, it was concluded that both SWAT and ANN were suitable. The more arid the catchment, the lower the performances obtained in the hydrological models, which is similar to the experience reported by Pérez-Sánchez et al, (2017) [61].…”
Section: Comparison Of Model Performancesupporting
confidence: 90%
“…Therefore, scenario 1 was the selected architecture for LRB. However, the performance levels of ANN models for HSRB were lower in general because modelling the hydrological response of arid and semi-arid regions, where evapotranspiration rates are high and precipitation is irregular and/or limited, is especially complex [61]. The selected model for HSRB was scenario 3 where NSE and RMSE were better than those obtained in other proposed scenarios.…”
Section: Input Selection Training and Validation Of Ann Modelsmentioning
confidence: 99%
“…When comparing total volumes observed and modelled (Table 6) with REV, previous findings were confirmed. GR2M appeared to be the best model for all the watersheds [24], and, although AEMET_G did not give the lowest percentage in all cases, the difference was never over 5% compared with the rest of the datasets. TRMM and MSWEP results for GR2M were below 15% in all watersheds, except in GAR, where CFSR volume error was −1.59%, 20% lower than the others.…”
Section: Evaluation Of the Simulated Streamflow Using Mwbmmentioning
confidence: 79%
“…It also includes some of the driest areas in the southeast, with a marked summer drought, and the rainiest areas in Europe in the northeast [24]. Four basins distributed over Peninsular Spain were used as study areas.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation